Microstructural characterization and mechanical properties of 3D-printed co-cr-mo parts by electron beam melting (EBM) - Muhammad Hanif Bin Abdul Wahab (2016)
Electron Beam Manufacturing (EBM), a newly introduced form of additive manufacturing, is gaining more interest in numerous industries due to it’s great potential applications in orthopaedic implants, dental implants and aerospace components. However, little has been done to study its microstructure and how it relates to its physical properties. This study investigates the mechanical properties and its relation to the microstructure of as-built EBM-fabricated CoCr parts of varying thicknesses. The fabricated parts were found to have less than 1% porosity. Microstructural characterization was carried out using Scanning Electron Microscopy (SEM) and the Optical Microscope (OM). It was found that the microstructure consists mainly of face-centred cubic columnar grains as well as continuous carbide thin films at grain boundaries and inter-dendritic regions.